Exploiting Natural Cross-reactivity between Human Immunodeficiency Virus (HIV)-1 p17 Protein and Anti-gp41 2F5 Antibody to Induce HIV-1 Neutralizing Responses In Vivo - Verrier, Bernard; Paul, Stéphane; Terrat, Céline; Bastide, Liza; Ensinas, Agathe; Phelip, Capucine; Chanut, Blandine; Bulens-Grassigny, Laura; Jospin, Fabienne; Guillon, Christophe (Frontiers in Immunology, 2017)
Anti-p17 antibodies are able to neutralize human immunodeficiency virus (HIV) entry in a mouse model. In this study, we identified a region of sequence similarity between the epitopes of anti-p17 neutralizing antibodies and anti-gp41 neutralizing 2F5 antibody, and verified cross-reactivity between p17 and 2F5 in vitro. The p17 sequence was modified to increase sequence identity between the p17 and 2F5 epitopes, which resulted in enhanced cross-reactivity in vitro. Immunogenicity of wild-type and modified p17 were characterized in a rabbit model. Both wild-type and mutated p17 induced anti-gp41 responses in rabbits; sera from these animals reacted with gp41 from different HIV clades. Moreover, introduction of the 2F5 sequence in p17 resulted in induction of antibodies with partially neutralizing activity. Based upon these data, we suggest that the natural cross-reactivity between HIV-1 p17 protein and 2F5 antibody can be exploited to induce antibodies with neutralizing activity in an animal model.